Analisis Kritis terhadap Ratio Decidendi Hakim dalam Putusan Kasasi Nomor 161 K/Pdt.Sus-HKI/2023 serta Implikasinya terhadap Penegakan Hukum Merek di Indonesia - Evita Ai Takeshita Simanjutak; Ni Putu Sawitri Nandari; I Gede Agus Kurniawan; Bagus Gede Ari Rama (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The inconsistency in judicial reasoning regarding trademark disputes in Indonesia, particularly in determining similarity and bad faith, raises concerns about legal certainty and protection. This study aims to critically analyze the ratio decidendi of the Supreme Court Cassation Decision Number 161 K/Pdt.Sus-HKI/2023 and examine its implications for trademark law enforcement. The research employs a normative juridical method using statute, conceptual, and case approaches, with qualitative analysis of legal materials and judicial considerations. The findings indicate that the judges primarily relied on formal parameters, such as similarity in essence and indications of bad faith, while insufficiently addressing substantive aspects, including consumer protection and the broader objectives of trademark law. Furthermore, the interpretation of well-known trademark criteria and evidentiary standards appears inconsistent, potentially leading to divergent applications in future cases. This decision strengthens legal protection for trademark owners but also highlights the need for more coherent and comprehensive judicial reasoning. Therefore, improving interpretative guidelines and strengthening analytical approaches in judicial decision-making are essential to ensure greater legal certainty, fairness, and effectiveness in trademark law enforcement in Indonesia.